Analisis Kepuasan Pengunjung Taman Margasatwa dan Budaya Kinantan (TMSBK) Kota Bukittinggi, Sumatera Barat - Waldy, Nur Amaliya; Sihombing, Irene Hanna H.; Widawati, Ida Ayu Putri (Tulisan Ilmiah Pariwisata (TULIP), 2023)
This background of this research was motivated by visitor dissatisfaction when visiting the Kinantan Wildlife and Cultural Park (TMSBK) in Bukittinggi City. The Kinantan Wildlife and Cultural Park is a zoo located in the City of Bukittinggi, West Sumatra. This study aims to analyze visitor satisfaction TMSBK. The type of research used in this study is qualitative. The data collected is primary data. The population of this study was respondents who had visited TMSBK. The research sample totaled of 100 visitors. Data collection techniques were carried out using a questionnaire with a Likert scale that had been tested for validity and reliability. The data from this study were processed using descriptive analysis techniques. The results of this study indicate that visitor satisfaction at the Kinantan Wildlife and Cultural Park Bukittinggi City, indicates that in general it has not met visitor expectations. Visitor satisfaction at the Kinantan Wildlife and Cultural Park Bukittinggi City, is not achieved in terms of factors and indicators of visitor satisfaction, namely animals and animal enclosures in Poorly maintained TMSBK, unsatisfactory responsiveness of officers to visitors, unavailability of public transportation, unavailability of special parking lots for visitors and unavailability of food court facilities where locl business actors sell goods in the TMSBK area. It can be described that visitor satisfaction based on TMSBK respondents’ assessment has not provided satisfaction to visitors.